THE EFFECT OF ENTREPRENEURIAL ORIENTATION AND MARKET ORIENTATION ON SME BUSINESS PERFORMANCE THROUGH PRODUCT INNOVATION AS A MEDIATING VARIABLE IN JEPARA'S FURNITURE CRAFTSMEN - Sri Swasta; Andi Wijayanto; Sari Listyorini (SEAN Institute, 2023)
Market orientation refers to entrepreneurs' efforts to understand market needs, develop products to meet consumer demands, and build relationships with customers. The aim of this research is to examine how entrepreneurial orientation and market orientation influence the business performance of SMEs in the context of furniture craftsmen in Jepara. This study investigates whether product innovation plays a mediating role in the relationship between entrepreneurial orientation, market orientation, and business performance. The research method employed is survey or interviews with furniture craftsmen in Jepara. The research sample can be selected randomly or using appropriate sampling techniques. To gather data, entrepreneurs can be provided with open-ended questionnaires on entrepreneurial orientation, market orientation, product innovation, and business performance. Data collection techniques can be analyzed using triangulation techniques. The results of the study can provide insights into the importance of entrepreneurial orientation and market orientation in enhancing the business performance of SMEs in the furniture craftsmen sector. Furthermore, this research can identify the role of product innovation as a mediating variable that connects entrepreneurial orientation and market orientation with business performance.